Social Reality Construction of Corona Virus Handling News in Natuna on Republika Online and CNNIndonesia.Com - Firman Katon; Ulfa Yuniati; Nora Meilinda Hardi (Universitas Ahmad Dahlan, 2022)
Indonesia evacuated and observed Indonesian citizens from Wuhan in Natuna, Riau Islands (Kepri), regarding the spread of the Coronavirus in China. Hearing the news, the residents of Natuna were worried and staged a demonstration. The report analyzed in this study is news on Republika Online and CNNIndonesia.com, spanning January 29 - February 16, 2020. This study uses the constructionist paradigm and Zongdang Pan and Gerald M. Kosicki's framing analysis techniques. This study indicates that Republika Online shows overcoming the problem of the policy of determining Natuna in carrying out framing. At the same time, CNNIndonesia.com, in its reporting, is more directed to the worries/anxieties experienced by Natuna residents. Based on the syntactic structure, Republika Online compiled facts regarding the absence of information/coordination regarding the quarantine of Indonesian citizens in Wuhan. At the same time, CNNIndonesia.com Residents rejected the policy of establishing Natuna as a place of observation for Indonesian citizens from Wuhan. In the Republika Online script element, the Natuna Residents refused to quarantine and observe Indonesian citizens from Wuhan because they were worried about contracting the Coronavirus. At the same time, CNNIndonesia.com published that the Government was the perpetrator in the issue of determining Natuna. Based on Republika Online's Thematic, the concerns of Natuna residents were caused by misinformation received. At the same time, CNNIndonesia.com had an error in implementing the Observation policy for Indonesian citizens from Wuhan in Natuna. Based on the Rhetoric, Republika Online provides facts that the Government cares and is suitable for Natuna residents and Indonesian citizens from Wuhan. At the same time, CNNIndonesia.com says that